Biometrics and the ecology of corruption: A posthuman study of the E-KTP Scandal - Fitrilya Anjarsari; Estiningtyas Sholikhah (Integritas: Jurnal Antikorupsi, 2025)
This article analyzes Indonesia’s e-KTP electronic ID corruption scandal as a critical test case for digital citizenship in a corruption-prone, postcolonial democracy. Drawing on a qualitative case study of court verdicts, procurement documents, official reports, and investigative journalism, it reconstructs how biometric devices, databases, procurement contracts, party networks, and legal loopholes became tightly coupled in ways that enabled large-scale fraud. Adopting a posthumanist perspective, the study understands corruption not only as the moral failure of individual officials but as an emergent effect of a sociotechnical assemblage in which human actors, code, hardware, and rules co-produce opportunities for rent-seeking. In dialogue with human-in-the-loop approaches to digital governance, the article shows that placing humans at key decision points does little to prevent abuse when those humans are embedded in predatory political and business arrangements. The analysis argues that the e-KTP case exposes the fragility of technological promises that frame biometric identification as a neutral instrument of efficiency, transparency, and security. Instead, the scandal demonstrates how digital infrastructures can be colonized by existing patronage and capital interests unless they are designed and governed with explicit attention to power, accountability, and data justice. By bringing corruption studies into conversation with critical posthumanist thought, the article offers a framework for evaluating future identity and e-government projects in Indonesia and comparable settings.